Respuesta :
hey there!
This can be written as [tex] n^{2}-(7)^{2}[/tex]
This is in form of [tex]\fbox{a^{2}-b^{2}}[/tex] , it can be expanded as [tex]\fbox{(a-b)(a+b)}[/tex]
=> (n-7)(n+7)=0
=> n -7 = 0 or n + 7 = 0
=> n = 7 or n = -7
So option 7 , -7 are correct.
Hope this is clear :)
Have a good day:)
This can be written as [tex] n^{2}-(7)^{2}[/tex]
This is in form of [tex]\fbox{a^{2}-b^{2}}[/tex] , it can be expanded as [tex]\fbox{(a-b)(a+b)}[/tex]
=> (n-7)(n+7)=0
=> n -7 = 0 or n + 7 = 0
=> n = 7 or n = -7
So option 7 , -7 are correct.
Hope this is clear :)
Have a good day:)